2018
DOI: 10.21037/jtd.2018.03.50
|View full text |Cite
|
Sign up to set email alerts
|

Short-term one-lung ventilation does not influence local inflammatory cytokine response after lung resection

Abstract: Background: One-lung ventilation (OLV) is a ventilation procedure used for pulmonary resection which may results in lung injury. The aim of this study was to evaluate the local inflammatory cytokine response from the dependent lung after OLV and its correlation to VT. The secondary aim was to evaluate the clinical outcome of each patient. Methods: Twenty-eight consecutive patients were enrolled. Ventilation was delivered in volume-controlled mode with a VT based on predicted body weight (PBW). 5 cmH 2 O positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The optimal cutoff value identified was 157.5 minutes for OLV. Fiorelli et al 12 found that short-term OLV does not influence local inflammatory cytokine responses after lung resection. The duration of OLV in that study was about 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal cutoff value identified was 157.5 minutes for OLV. Fiorelli et al 12 found that short-term OLV does not influence local inflammatory cytokine responses after lung resection. The duration of OLV in that study was about 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…However, different durations of OLV have different effects on the lung injury. For lung resection surgery, Fiorelli et al 12 showed that short-term OLV does not influence the local inflammatory cytokine response, while a retrospective analysis identified the duration of OLV as a risk factor for postoperative acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). 6 There are no trials assessing the effect of duration of OLV on postoperative pulmonary complications after McKeown esophagectomy.…”
Section: Introductionmentioning
confidence: 99%
“…A small randomized study in VATS patients found that the combination of protective ventilation with a recruitment maneuver was associated with attenuated inflammatory responses, compared with either conventional ventilation or protective ventilation alone (Kim et al 2019 ). By contrast, a non-randomized study in 28 patients found no significant difference in local inflammatory cytokine responses between lung resection patients receiving protective or conventional ventilation (Fiorelli et al 2018 ).…”
Section: Intraoperative Carementioning
confidence: 95%
“…However, the intrapulmonary shunt changes during OLV were not considered in previous studies. Furthermore, recent studies have demonstrated that an individualized PEEP adjustment is associated with better oxygenation (2), decreased intrapulmonary shunt (6), lower driving pressure (7), lower or no inflammatory responses (12,13) and lower incidence of postoperative pulmonary complications (14,15). Conversely, an individualized PEEP titration, will not completely prevent atelectasis formation in the particular population (16,17).…”
Section: Introductionmentioning
confidence: 99%